The Mātṛkā Dance: Conceptualizing the Dancing Body of the Goddess - Funes Maderey, Ana Laura (Sophia, 2024)
Conceptualizing the image of a dancing Supreme Goddess in the Hindu tradition presents a philosophical challenge because it demands a coherent rational reconciliation between her nature as continuously changing into multiple forms and the realm of pure, absolute, never-changing, formless being. Different strategies have been proposed in the history of philosophy in India. This paper analyzes the image of the dancing Goddess as it appears in the Devī Māhātmya and in the Tantric iconography of the Goddess Kālī. An argument is developed to show that Śākta philosophy resolves this tension through a radical non-dualist understanding of the role that a mental image (vikalpa) plays in accessing supreme reality.